Assessing lethal doses of the baculovirus MaviMNPV and the effect of its combination with neem oil on the survival of Maruca vitrata (Fabricius) (Lepidoptera: Crambidae) larval stages in laboratory - Kindozandji, A.; Dannou, E.A.; Nondichao, A.N.; Amevoin, K.; Glitho, I.A.; Srinivasan, R.; Pittendrigh, B.R.; Tamò, Manuele (Springer, 2022)
Cowpea production is limited by predation from several insect pests, including Maruca vitrata (F.) (Lepidoptera: Crambidae) as one of the most destructive. The present study aimed to assess the pesticidal effect of neem oil and the baculovirus MaviMNPV (separately and in combination) on M. vitrata under laboratory conditions. Eight treatments in a 4-replicate randomized block design (including control) were assessed at each of the five M. vitrata larval stages. Neem oil induced larval mortality ranging from 41.50 ± 2.50% to 97.08 ± 2.00%, with the lower values in L4 and L5, while MaviMNPV induced larval mortality varying from 15 ± 0.63% to 100 ± 00% (depending on larval stages). Used in combination, induced larval mortality was higher still (from 28.33 ± 4.40% to 100 ± 00%), suggesting a synergistic or additive action. Cox regression also indicated that MaviMNPV larval mortality was dose-dependent when applied at large stages L1, L2, and L3.